Implementasi Kurikulum Berbasis KKNI pada Program Studi Pendidikan Bahasa Arab: Studi Evaluatif - Musta’in, Musta’in; Husnan, Umar (Jurnal Multidisiplin Ibrahimy, 2026)
Evaluation of the implementation of the Indonesian National Qualifications Framework (KKNI)-based Curriculum plays a crucial role in ensuring the quality of higher education. This study was conducted in the Arabic Language Education Study Program at STAI Ali bin Abi Thalib Surabaya to analyze the effectiveness and suitability of the KKNI curriculum implementation to established standards. The assessment focused on the extent to which the curriculum implementation had achieved the KKNI-based Graduate Learning Outcomes (CPL). This study is important to provide empirical data as recommendations for curriculum improvement in order to produce qualified and competitive Arabic Language graduates. The approach used in this study was descriptive qualitative with the CIPP (Context, Input, Process, Product) evaluation framework. Research data were obtained through in-depth interviews, direct observation, and documentation studies of the curriculum and learning tools. The research subjects consisted of lecturers, study program secretaries, education staff, students, and curriculum documents used in the learning process. The results showed that the implementation of the KKNI-based curriculum has generally gone quite well. In terms of context and input, lecturers' understanding and institutional readiness are considered good, although socialization to students is still limited. In terms of process, Student-Centered Learning (SCL) has begun to be implemented, but it is not yet optimal in all courses. Meanwhile, in terms of product, research results show that the implementation of the KKNI-based curriculum has produced graduates who meet the Graduate Learning Outcomes (CPL). Based on tracer study data, the majority of alumni work as educators and education personnel, and possess applied competencies relevant to the needs of the workforce.